UVA1 exposures change gene expression and circadian time-related protein CRY2 in human skin - Haapasalo, Annina; Liong, Olivia; Jernman, Juha; Ylianttila, Lasse; Snellman, Erna; Pasternack, Rafael; Partonen, Timo; Karisola, Piia (Elsevier, 2026)
Background: The molecular effects involved in the cellular response to ultraviolet A1 (UVA1) exposures in human skin are incompletely understood.
Objectives: We examined the molecular mechanisms underlying the physiological effects of low-dose UVA1 exposures in human skin in vivo by observing especially the contribution of diurnal preference and circadian clock-related genes and proteins.
Methods: Healthy volunteers (n = 21) were exposed to a cumulative dose of 30 J/cm2 of UVA1 (340–400 nm) or 0.42 J/cm2 of violet light (390–440 nm, n = 20). Immunohistochemistry, transcriptomics, real-time quantitative PCR (RT-qPCR), gene enrichment analyses, and cellular deconvolution were performed from buttock skin samples at the start and after three days of consecutive morning exposures.
Results: UVA1 exposures significantly increased CRY2 and P53 protein staining in the IHC and yielded 16 differentially expressed genes (DEGs) involved in melanogenesis (Pmel, Tyr, Tyrp1), cytotoxic protection (Aldh3a2/a1, Cdk7, Nampt, Bcl2a1, Ackr4, Rpa3, Ube2q2) and circadian rhythm (Csnk1e, Nampt) in the skin compared to unexposed skin samples. RT-qPCR was performed for Aldh3a1, Aldh3a2, Tyr, Tyrp1 and Nampt to strengthen the transcriptomic results. No DEGs were found when exploring the underlying adipose tissue or the violet light-exposed group. In cellular deconvolution analysis, the fraction of eosinophils and M0 macrophages was increased after UVA1 exposures, with M0 macrophages especially among morning-types.
Conclusion: Low-dose UVA1 exposures caused changes in gene expression, P53 and CRY2 protein production, and cell type fractions in the skin, but the effects did not reach the subcutaneous adipose tissue. Since the solar UVR dominates in UVA, it is essential to continue to protect the skin from harmful solar agents, regardless of the diurnal preference.